Effects of pulsed electric field processing on microbial survival, quality change and nutritional characteristics of blueberries. (April 2017) - Jin, Tony Z.; Yu, Yuanshan; Gurtler, Joshua B.
Abstract: Whole fresh blueberries were treated using a parallel pulsed electric field (PEF) treatment chamber and a sanitizer solution (60 ppm peracetic acid [PAA]) as PEF treatment medium with square wave bipolar pulses at 2 kV/cm electric field strength, 1μs pulse width, and 100 pulses per second for 2, 4, and 6 min. The effects of PEF on native microbiota and artificially-inoculated Escherichia coli K12 and Listeria innocua populations on blueberries were determined. Color, texture, anthocyanins and total phenolic compound concentrations were also evaluated. The combination of PEF and PAA was able to achieve up to 3 log reduction of E. coli and Listeria as well as 2 log/g reduction of native microbiota. PEF treatments did not cause any changes in color and appearance of the blueberries. The treatments did, however, cause the blueberries to soften in texture. Anthocyanins and phenolic compounds in blueberries increased by 10 and 25%, respectively, after PEF treatments. The results demonstrate the potential of PEF applications to enhance the safety and improve the quality and nutritional value of fruits and their derived products. Highlights: Sanitizer solution was used as PEF treatment medium for fresh whole blueberries. 2–3 log reductions of natural microflora, E. coli, Listeria were achieved. No changes in color and appearance of the blueberries were observed. Anthocyanins and phenolic compounds increased after PEF treatments. Sanitizer solution + PEF is potential to improve safety, quality and nutritional value.